Supported catalyst, preparation method thereof and proton exchange membrane fuel cell
By using the nickel and platinum activity ingredients as the load catalyst of the kernel and platinum atomic layer as the shell layer, the problem of complex catalyst preparation, unstable structure, and low oxygen reduction activity in existing technology, realize high -activity and stability catalyst catalysts , Reduce the cost of fuel cells.
Patent Information
- Application Number
- CN202211167823.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-09-23
AI Technical Summary
The existing core-shell catalyst preparation method is complex and cumbersome, the catalyst structure is unstable and the oxygen reduction reaction activity is low.
A supported catalyst using nickel-platinum active ingredient as the core and platinum atomic layer as the shell. The crystal structure of the core is a close-packed hexagonal structure. The nickel-platinum active ingredient is loaded on a carbon or metal oxide carrier.
It improves the oxygen reduction reaction activity and stability of the catalyst, reduces the use of precious metal platinum, saves the cost of fuel cells, and promotes the commercialization of fuel cells.
Smart Images

Figure CN115986150B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a supported catalyst, a preparation method thereof and a proton exchange membrane fuel cell. Background Art
[0002] Fuel cells can directly and efficiently convert the chemical energy of hydrogen into electrical energy, with water being the only byproduct. Therefore, powering a car with a fuel cell is completely pollution-free, which has huge environmental benefits. In addition, fuel cells are more efficient than gasoline internal combustion engines. In the long run, a transportation system powered by hydrogen and fuel cells will bring significant economic and environmental benefits.
[0003] However, the technical barriers and high cost of fuel cells limit its large-scale market application. In order to reduce costs, what needs to be done in terms of catalysts is to improve the reaction activity and reduce the use of precious metal platinum (Pt). The most commonly used method is to alloy Pt with transition metals (including Fe, Co, Ni, Cr, etc.) to obtain binary or ternary alloy catalysts. Another developed method is to wrap the Pt atomic layer on the surface of nanoparticles to form a core-shell structure. In particular, when Pt is deposited on an alloy substrate to form a Pt shell structure, lattice compression occurs due to the lattice mismatch between Pt and the substrate. The resulting surface strain affects the charge state, thereby changing the binding energy of the adsorbate on Pt, which is crucial to improving the electrocatalytic activity of the Pt catalyst in the fuel cell cathode oxygen reduction reaction (ORR). At the same time, using the alloy substrate as the core can effectively improve the stability of the catalyst and avoid the dissolution and loss of the core. In addition, this core-shell structure can improve the utilization rate of precious metals and reduce the usage, which is conducive to reducing the cost of catalysts and promoting the commercialization of fuel cells.
[0004] Existing documents (publication number CN110890558A) disclose a supported platinum-based core-shell catalyst and its preparation method. The cobalt precursor is dissolved in an alcohol-water mixed solution, a treated carbon carrier is added, and the pH is adjusted to alkaline reflux treatment for 2 to 20 hours to obtain a slurry of a cobalt-carbon mixture; the pH of the platinum precursor aqueous solution is adjusted to alkaline, the cobalt-carbon mixture slurry is mixed evenly, and the pH value is adjusted to alkaline again; then it is transferred to an autoclave for hydrothermal reaction for 1 to 20 hours, and the reaction temperature is 100 to 200 ° C; washing and drying to obtain a carbon-supported platinum-cobalt mixture; heat-treating the prepared carbon-supported platinum-cobalt mixture in a reducing gas to obtain carbon-supported platinum-cobalt alloy nanoparticles; the reduction-treated carbon-supported platinum-cobalt mixture is placed in an acidic aqueous solution and soaked for 1 to 40 hours, and then washed and dried to obtain a carbon-supported platinum-cobalt nanocore-shell catalyst. This synthesis method is cumbersome to operate, and it takes a long time to go through multiple procedures such as multiple solution mixing and pH adjustment, reaction, heat treatment, pickling, etc., and it also requires the use of an autoclave, which is dangerous. In addition, a dense platinum layer cannot be formed on the surface of the nanoparticles of the core-shell catalyst obtained by acid treatment, which affects the stability of the catalyst.
[0005] Existing document (publication number CN109037715A) proposes a catalyst and preparation method for ultra-low platinum content for fuel cells, after heat treatment of metal source with oleylamine and trioctylphosphine at 180-270°C, precious metal salt is added dropwise, centrifuged and dried to form spherical nanoparticles, and then vacuum pre-calcined and reduced to load the nanoparticles on the surface of graphite electrode, and then electrochemically treated in acid solution to form a single atomic layer of copper by underpotential deposition of copper on the surface of electrode, and finally soaked in potassium chloroplatinate to replace copper with platinum, forming a multilayer core-shell structure of transition metal-precious metal-platinum, and finally obtained the desired catalyst by carbon loading. The synthesis method is complicated, and needs to go through a series of processes such as solvent high temperature thermal reaction, centrifugal drying, graphite electrode loading, copper underpotential deposition, replacement of platinum, catalyst peeling from electrode surface, and washing and drying again; and the nanoparticles need to be loaded on the surface of graphite electrode for underpotential deposition of copper, and this special method makes the amount of synthesized catalyst very small.
[0006] Therefore, it is necessary to study and develop a supported catalyst with a core-shell structure that has a simple preparation method and a stable structure, which is of great significance for improving the activity and durability of the catalyst in oxygen reduction reactions. Summary of the invention
[0007] The main purpose of the present invention is to provide a supported catalyst, a preparation method thereof and a proton exchange membrane fuel cell, so as to solve the problems that the preparation method of the core-shell catalyst in the prior art is complicated and the operation is cumbersome, and the existing catalyst with a core-shell structure is unstable and has poor oxygen reduction reaction activity.
[0008] In order to achieve the above-mentioned purpose, the present invention provides a supported catalyst on the one hand, which includes a nickel-platinum active ingredient and a carrier, and the nickel-platinum active ingredient is loaded on the surface of the carrier; from the inside to the outside, the nickel-platinum active ingredient includes a core and a shell; the core is a nickel element or a nickel alloy, the nickel alloy includes nickel elements and non-nickel metal elements, the shell is a platinum atomic layer, and the shell is coated on the surface of the core; the crystal structure of the core is a close-packed hexagonal structure.
[0009] Furthermore, the molar ratio of the core to the shell is (2-10):1; preferably, the molar ratio of the core to the shell is (2-6):1.
[0010] Furthermore, based on the total weight of the supported catalyst, the loading amount of the nickel-platinum active component is 30-60 wt%.
[0011] Furthermore, the molar ratio of nickel element to non-nickel metal element is ≥10:1, preferably (10-20):1; preferably, the non-nickel metal element is selected from one or more of the group consisting of elements in Group IIA, Group IIIA, Group IVA, Group VA, Group VIII, Group IB, Group IIIB, Group IVB and Group VB; more preferably, the non-nickel metal element is selected from one or more of the group consisting of Sr, Ga, Sn, Bi, Fe, Co, Cu, Au, Sc, La, Ce, Sm, Ti, Zr, V, Mo and W.
[0012] Furthermore, the average particle size of the nickel-platinum active component is 5 to 30 nm; preferably, the average particle size of the nickel-platinum active component is 5 to 20 nm.
[0013] Furthermore, the number of platinum atomic layers is 1 to 6 layers, preferably 2 to 4 layers.
[0014] Furthermore, the carrier is a carbon carrier and / or a metal oxide carrier; the carbon carrier is selected from one or more of the group consisting of activated carbon, carbon black, graphite, graphene and acetylene black; the metal oxide carrier is selected from one or more of the group consisting of doped SnO2, TiO2, Ti4O7, CeO2, NbO, NbO2, Nb2O3, Nb2O5 and WO3; preferably, the doped SnO2 includes a doping element, and the doping element is selected from one or more of the group consisting of Sb, Nb, In and W.
[0015] In order to achieve the above-mentioned purpose, another aspect of the present invention also provides a method for preparing the above-mentioned supported catalyst, which comprises: under a first inert atmosphere, mixing a nickel salt, an organic solvent, a first alkylamine, an alkyl phosphide and an optional non-nickel metal salt and performing a staged temperature treatment to obtain a nickel-based active ingredient solution, wherein the non-nickel metal element in the non-nickel metal salt is an element type that can form an alloy with the nickel element; the organic solvent is selected from one or more of the group consisting of octadecene, phenyl ether and benzene ether; under a second inert atmosphere, mixing a platinum salt, a reducing agent and a second alkylamine and performing a first heating treatment to obtain a platinum precursor solution; under a third inert atmosphere, mixing the platinum precursor solution with the nickel-based active ingredient solution and performing a second heating treatment to obtain a nickel-platinum active ingredient; and loading the nickel-platinum active ingredient on the surface of the carrier to obtain a supported catalyst.
[0016] Furthermore, the nickel salt is selected from one or more of the group consisting of nickel acetylacetonate, nickel sulfate, nickel acetate, nickel chloride and nickel acetate; the platinum salt is selected from one or more of the group consisting of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, platinum acetylacetonate and platinum nitrate.
[0017] Furthermore, the staged temperature increase treatment includes a first temperature increase treatment and a second temperature increase treatment; the first temperature increase treatment includes: heating the reaction system to 80-100°C and then performing a vacuum treatment, and maintaining it for 5-60 minutes; the second temperature increase treatment includes: heating the mixed solution obtained after completing the first temperature increase treatment to 180-250°C, and maintaining it for 0.5-3 hours; preferably, the vacuum degree of the vacuum treatment is 80-200 mbar; preferably, the molar ratio of the nickel salt, the solvent, the first alkylamine and the alkyl phosphide is 1:(20-50):(10-50):(0.1-1); more preferably, the first alkylamine is selected from one or more of the group consisting of oleylamine, dodecylamine, hexadecylamine, octadecylamine, octadecylamine and trioctylamine; the alkyl phosphide is selected from one or more of the group consisting of trioctylphosphine, trioctylphosphine oxide and tributylphosphine.
[0018] Furthermore, the reaction system of the first heat treatment also includes a surfactant; preferably, the molar ratio of platinum salt, reducing agent, alkylamine and surfactant is 1:(8-20):(10-40):(10-20); preferably, the temperature of the first heat treatment is 50-100°C and the time is 5-60 min; more preferably, the reducing agent is selected from 1,2-dodecanediol and / or 1,2-tetradecanediol; the second alkylamine is selected from one or more of the group consisting of oleylamine, dodecylamine, hexadecylamine and octadecylamine; the surfactant is selected from one or more of the group consisting of oleic acid, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide.
[0019] Furthermore, the temperature of the second heat treatment is 150-220° C., and the time is 1-3 hours.
[0020] Another aspect of the present invention provides a proton exchange membrane fuel cell, which comprises the above-mentioned supported catalyst or the supported catalyst prepared by the above-mentioned method for preparing the supported catalyst.
[0021] By applying the technical solution of the present invention, the nickel-platinum active component has a nickel element or a nickel alloy as a core, and a platinum atomic layer as a shell layer coated on the surface of the core. Since the crystal structure of the core is a hexagonal close-packed structure (hcp), the regulation of the geometric effect and electronic effect of the nickel-containing core on the platinum-containing shell layer can improve the oxygen reduction reaction activity of the supported catalyst, and the core-shell structure can reduce the use of precious metal platinum, save the cost of fuel cells, and thus contribute to the commercialization and promotion of fuel cells.
[0022] Compared with catalysts with a face-centered cubic (fcc) core, catalysts with a hexagonal close-packed (hcp) core have better oxygen reduction activity. This is mainly attributed to the geometric and electronic effects of the nickel-containing core of the hcp crystal on platinum, which can shrink the lattice spacing of the platinum atomic layer and increase the number of d-orbital holes of the platinum atoms. Compared with platinum atoms regulated by the fcc-type core, the position of the center of the platinum d band is lower, which is more conducive to the dissociative adsorption of oxygen, and thus has a higher oxygen reduction reaction activity.
[0023] In addition, loading the nickel-platinum active component on the surface of the carrier can improve the dispersibility of the nickel-platinum active component, and there is a strong interaction between the nickel-platinum active component and the carrier, thereby enhancing the stability of the supported catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0025] Figure 1 The hcp-Ni prepared in Example 1 is shown 100 Mo 6.7 Transmission electron microscopy (TEM) image of the inner core;
[0026] Figure 2 The hcp-Ni prepared in Example 1 is shown 100 Mo 6.7 @Pt 25 Transmission electron microscopy (TEM) image of the nickel-platinum active component;
[0027] Figure 3 The hcp-Ni prepared in Example 1 is shown 100 Mo 6.7X-ray diffraction (XRD) pattern of the inner core;
[0028] Figure 4 The hcp-Ni prepared in Example 1 is shown 100 Mo 6.7 @Pt 25 / Transmission electron microscopy (TEM) image of C supported catalyst;
[0029] Figure 5 The fcc-Ni prepared in Comparative Example 1 is shown. 100 Mo 6.7 TEM image of the inner core;
[0030] Figure 6 The fcc-Ni prepared in Comparative Example 1 is shown. 100 Mo 6.7 @Pt 25 TEM image of the nickel-platinum active component;
[0031] Figure 7 The fcc-Ni prepared in Comparative Example 1 is shown. 100 Mo 6.7 XRD pattern of the inner core. DETAILED DESCRIPTION
[0032] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0033] As described in the background technology, the preparation method of the existing core-shell catalyst has the problems of complex process and cumbersome operation, and the catalyst structure of the existing core-shell structure is unstable and the activity of oxygen reduction reaction is poor. In order to solve the above technical problems, the present application provides a supported catalyst, which includes a nickel-platinum active component and a carrier, and the nickel-platinum active component is loaded on the surface of the carrier; from the inside to the outside, the nickel-platinum active component includes a core and a shell; the core is a nickel element or a nickel alloy, the nickel alloy includes nickel elements and non-nickel metal elements, the shell is a platinum atomic layer, and the shell is coated on the surface of the core; the crystal structure of the core is a close-packed hexagonal structure.
[0034] The nickel-platinum active component has a nickel core or a nickel alloy as a core, and a platinum atomic layer as a shell covering the surface of the core. Since the crystal structure of the core is a hexagonal close-packed structure (hcp), the regulation of the geometric effect and electronic effect of the nickel-containing core on the platinum-containing shell can improve the oxygen reduction reaction activity of the supported catalyst, and the core-shell structure can reduce the use of precious metal platinum, save the cost of fuel cells, and thus contribute to the commercialization of fuel cells.
[0035] Compared with catalysts with a face-centered cubic (fcc) core, catalysts with a hexagonal close-packed (hcp) core have better oxygen reduction activity. This is mainly attributed to the geometric and electronic effects of the nickel-containing core of the hcp crystal on platinum, which can shrink the lattice spacing of the platinum atomic layer and increase the number of d-orbital holes of the platinum atoms. Compared with platinum atoms regulated by the fcc-type core, the position of the center of the platinum d band is lower, which is more conducive to the dissociative adsorption of oxygen, and thus has a higher oxygen reduction reaction activity.
[0036] In addition, loading the nickel-platinum active component on the surface of the carrier can improve the dispersibility of the nickel-platinum active component, and there is a strong interaction between the nickel-platinum active component and the carrier, thereby enhancing the stability of the supported catalyst.
[0037] In a preferred embodiment, the molar ratio of the core to the shell is (2-10): 1. The molar ratio of the core to the shell includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the coating effect and density of the platinum atomic layer on the core, inhibiting the precipitation of the nickel-containing core, and thus helping to improve its durability.
[0038] In order to further improve the coating effect and density of the platinum atomic layer on the inner core, further inhibit the precipitation of the nickel-containing inner core, and thus further improve its durability, preferably, the molar ratio of the core to the shell is (2-6):1.
[0039] In a preferred embodiment, the loading amount of the nickel platinum active component is 30-60wt% based on the total weight of the supported catalyst. The loading amount of the nickel platinum active component includes but is not limited to the above range, and limiting it within the above range is conducive to improving the oxygen reduction reaction activity of the supported catalyst. If the loading amount is too small, the catalytic layer of the membrane electrode in the proton exchange membrane fuel cell is thicker, and its proton conductivity and mass transfer and diffusion of oxygen are adversely affected; when the loading amount is too large, the nickel platinum active component is easier to agglomerate, which may lead to a reduction in electrochemical area and a reduction in metal utilization.
[0040] In a preferred embodiment, the molar ratio of nickel element to non-nickel metal element is ≥10:1, preferably (10-20):1. The molar ratio of nickel element to non-nickel metal element includes but is not limited to the above range, and limiting it within the above range is conducive to the inner core maintaining its hexagonal close-packed structure (hcp) unchanged, and the doping of non-nickel metal elements is conducive to further suppressing the problem of easy dissolution of the non-precious metal inner core, thereby enhancing the stability of the nickel-platinum active component in the supported catalyst.
[0041] In a preferred embodiment, the non-nickel metal elements include, but are not limited to, one or more of the group consisting of elements in Group IIA, Group IIIA, Group IVA, Group VA, Group VIII, Group IB, Group IIIB, Group IVB, and Group VB. Compared with other types, the use of the above-mentioned types of non-nickel metal elements is beneficial to further move the d-band center of the platinum atom in the platinum atomic layer toward the Fermi level through alloying, thereby improving the binding force between the above-mentioned supported catalyst and the oxygen-containing intermediate, and further improving the oxygen reduction reaction activity of the supported catalyst; at the same time, the above-mentioned types of non-nickel metal elements can form a more stable nickel alloy with the nickel element, thereby facilitating the inhibition of the precipitation of the nickel-based core, thereby improving the stability of the supported catalyst.
[0042] In order to further improve the stability of the supported catalyst and further improve the oxygen reduction reaction activity of the supported catalyst, preferably, the non-nickel metal elements include but are not limited to one or more of the group consisting of Sr, Ga, Sn, Bi, Fe, Co, Cu, Au, Sc, La, Ce, Sm, Ti, Zr, V, Mo and W.
[0043] In a preferred embodiment, the average particle size of the nickel-platinum active component is 5 to 30 nm. The average particle size of the nickel-platinum active component includes but is not limited to the above range, and limiting it within the above range is conducive to further improving the dispersibility of the nickel-platinum active component and further improving the oxygen reduction reaction activity of the supported catalyst.
[0044] In order to further improve the dispersibility of the nickel-platinum active component and further improve the oxygen reduction reaction activity of the supported catalyst, preferably, the average particle size of the nickel-platinum active component is 5 to 20 nm.
[0045] In a preferred embodiment, the number of platinum atomic layers is 1 to 6 layers, preferably 2 to 4 layers. The number of platinum atomic layers includes but is not limited to the above range. Limiting it within the above range is conducive to forming a dense platinum layer, thereby improving the durability of the supported catalyst; at the same time, it is conducive to exerting the geometric effect and strain effect of the core on the shell, thereby further improving the activity of the supported catalyst, and also conducive to reducing the amount of platinum, thereby further improving the utilization rate of the platinum element.
[0046] In a preferred embodiment, the carrier is a carbon carrier and / or a metal oxide carrier; the carbon carrier includes but is not limited to one or more of the group consisting of activated carbon, carbon black, graphite, graphene and acetylene black; the metal oxide carrier includes but is not limited to one or more of the group consisting of doped SnO2, TiO2, Ti4O7, CeO2, NbO, NbO2, Nb2O3, Nb2O5 and WO3.
[0047] Compared with other types, the use of the above preferred types of carriers is conducive to enhancing the interaction between the nickel-platinum active component and the carrier, thereby helping to improve the stability of the supported catalyst. When the carrier contains a metal oxide component, the metal in the metal oxide component can form a strong metal bond with Pt, which is conducive to improving the high potential durability of the supported catalyst.
[0048] In order to further improve the stability of the supported catalyst, preferably, the doped SnO2 includes a doping element, and the doping element includes but is not limited to one or more of the group consisting of Sb, Nb, In and W.
[0049] The second aspect of the present application also provides a method for preparing the above-mentioned supported catalyst provided by the present application, and the method for preparing the supported catalyst comprises: under a first inert atmosphere, mixing a nickel salt, an organic solvent, a first alkylamine, an alkyl phosphide and an optional non-nickel metal salt and performing a staged temperature increase treatment to obtain a nickel-based active ingredient solution, wherein the non-nickel metal element in the non-nickel metal salt is an element type that can form an alloy with the nickel element; the organic solvent includes but is not limited to one or more of the group consisting of octadecene, phenyl ether and benzyl ether; under a second inert atmosphere, mixing a platinum salt, a reducing agent and a second alkylamine and performing a first heating treatment to obtain a platinum precursor solution; under a third inert atmosphere, mixing the platinum precursor solution with the nickel-based active ingredient solution and performing a second heating treatment to obtain a nickel-platinum active ingredient; loading the nickel-platinum active ingredient on the surface of the carrier to obtain a supported catalyst.
[0050] Under the first inert atmosphere, nickel salt, solvent, first alkylamine, alkyl phosphide and optional non-nickel metal salt are mixed and subjected to stage temperature treatment, and a nickel-based active component solution of a close-packed hexagonal structure (hcp) is obtained in the presence of a specific solvent. Under the second inert atmosphere, platinum salt, reducing agent and second alkylamine are mixed and subjected to the first heat treatment so that each component can be fully dispersed and a uniform platinum precursor solution can be obtained. Under the third inert atmosphere, the platinum precursor solution is mixed with the nickel-based active component solution and subjected to the second heat treatment so that the platinum element in the platinum salt can be reduced, while being coated on the surface of the nickel-based active component and forming a dense platinum atomic layer, thereby obtaining a core-shell structure. The nickel-platinum active component is loaded on the carrier surface to obtain a supported catalyst provided by the present application.
[0051] The preparation method of the supported catalyst is simple in process and controllable in conditions. The core crystal structure that can be obtained in the presence of a specific solvent is a hexagonal close-packed structure (hcp). Since the core crystal structure is a hexagonal close-packed structure (hcp), the regulation of the geometric effect and electronic effect of the nickel-containing core on the platinum-containing shell can improve the oxygen reduction reaction activity of the supported catalyst. At the same time, the core-shell structure can reduce the use of precious metal platinum, save the cost of fuel cells, and thus contribute to the commercialization and promotion of fuel cells.
[0052] Compared with catalysts with a face-centered cubic (fcc) core, catalysts with a hexagonal close-packed (hcp) core have better oxygen reduction activity. This is mainly attributed to the geometric and electronic effects of the nickel-containing core of the hcp crystal on platinum, which can shrink the lattice spacing of the platinum atomic layer and increase the number of d-orbital holes of the platinum atoms. Compared with platinum atoms regulated by the fcc-type core, the position of the center of the platinum d band is lower, which is more conducive to the dissociative adsorption of oxygen, and thus has a higher oxygen reduction reaction activity.
[0053] In addition, loading the nickel-platinum active component on the surface of the carrier can improve the dispersibility of the nickel-platinum active component, and there is a strong interaction between the nickel-platinum active component and the carrier, thereby enhancing the stability of the supported catalyst.
[0054] Nickel salts and platinum salts can be selected from commonly used types in the art. In a preferred embodiment, the nickel salts include but are not limited to one or more of the group consisting of nickel acetylacetonate, nickel sulfate, nickel acetate, nickel chloride and nickel acetate; the platinum salts include but are not limited to one or more of the group consisting of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, platinum acetylacetonate and platinum nitrate.
[0055] In a preferred embodiment, the staged temperature rising treatment includes a first temperature rising treatment and a second temperature rising treatment; the first temperature rising treatment includes: heating the reaction system to 80-100°C and then performing a vacuum treatment, and maintaining it for 5-60 minutes; the second temperature rising treatment includes: heating the mixed solution obtained after completing the first temperature rising treatment to 180-250°C, and maintaining it for 0.5-3 hours.
[0056] Vacuuming the reaction system is beneficial to removing impurities generated by volatilization at high temperature in the solvent, so that the nickel-based active component obtained later has a more uniform particle size; it is also beneficial to remove oxygen dissolved in the solvent, thereby inhibiting the oxidation of the nickel-based active component, and facilitating the subsequent coating of the platinum atomic layer. In addition, using the above-mentioned specific temperature and time to treat the reaction system is beneficial to synthesizing nickel-based active components with more uniform particle sizes, and is also beneficial to the coating of platinum atomic layers, thereby inhibiting the oxidation of nickel-based active components and improving the oxygen reduction reaction activity of the supported catalyst.
[0057] In order to further improve the removal rate of oxygen and impurities, thereby forming a nickel-based active component with a more uniform particle size, preferably, the vacuum degree of the vacuum treatment is 80-200 mbar.
[0058] In a preferred embodiment, the molar ratio of the nickel salt, the solvent, the first alkylamine and the alkyl phosphide is 1:(20-50):(10-50):(0.1-1). The molar ratio of the nickel salt, the solvent, the first alkylamine and the alkyl phosphide includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the generation rate of the nickel-based active ingredient; it is also beneficial to obtain a nickel-platinum active ingredient with a more uniform particle size, thereby improving the activity.
[0059] In order to form a more uniform crystal inner core of a close-packed hexagonal structure, preferably, the first alkylamine includes but is not limited to one or more of the group consisting of oleylamine, dodecylamine, hexadecylamine, octadecylamine, octylamine and trioctylamine; the alkyl phosphide includes but is not limited to one or more of the group consisting of trioctylphosphine, trioctylphosphine oxide and tributylphosphine.
[0060] In a preferred embodiment, the reaction system of the first heat treatment further comprises a surfactant. The introduction of the surfactant into the reaction system is conducive to forming nickel-platinum active components with uniform particle size during the second heat treatment process.
[0061] In order to further improve the dispersibility of the platinum precursor and further improve the coating effect of the subsequent platinum atomic layer, preferably, the molar ratio of the platinum salt, the reducing agent, the alkylamine and the surfactant is 1:(8-20):(10-40):(10-20).
[0062] In a preferred embodiment, the temperature of the first heat treatment is 50-100° C., and the time is 5-60 min. The temperature and time of the first heat treatment include but are not limited to the above ranges, and limiting them within the above ranges is conducive to the dissolution of the solid platinum salt, the reducing agent and the surfactant, thereby forming a uniform platinum precursor solution, improving the dispersibility of the platinum precursor, and further improving the coating effect of the subsequent platinum atomic layer.
[0063] In order to improve the coating effect of the platinum atomic layer on the surface of the nickel-based active component and further improve the durability of the supported catalyst, preferably, the reducing agent includes but is not limited to 1,2-dodecanediol and / or 1,2-tetradecanediol; the second alkylamine includes but is not limited to one or more of the group consisting of oleylamine, dodecylamine, hexadecylamine and octadecylamine; the surfactant includes but is not limited to one or more of the group consisting of oleic acid, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide.
[0064] In a preferred embodiment, the temperature of the second heat treatment is 150-220°C and the time is 1-3 hours. The temperature and time of the second heat treatment include but are not limited to the above ranges. Limiting it within the above range is conducive to further improving the coating effect of the platinum atomic layer on the surface of the nickel-based active component, thereby further improving the durability of the supported catalyst; at the same time, it is conducive to further exerting the geometric effect and strain effect of the core on the shell, thereby further improving the activity of the supported catalyst, and further reducing the amount of platinum, thereby further improving the utilization rate of the platinum element.
[0065] In an optional embodiment, the nickel-platinum active ingredient is mixed with the carrier and stirred to load the platinum-nickel-based core-shell structure particles on the surface of the carrier, and then filtered, washed, dried, and subjected to a third heat treatment to obtain a supported catalyst. The use of stirring treatment is conducive to mixing the nickel-platinum active ingredient with the carrier more evenly, so that the nickel-platinum active ingredient is more evenly loaded on the surface of the carrier; the filtering and washing process is conducive to cleaning the surfactant and the solvent, thereby helping to improve the reaction activity. The third heat treatment is conducive to improving the crystallinity of the metal and enhancing the stability of the supported catalyst, thereby obtaining the supported catalyst provided by the present application.
[0066] In order to enhance the interaction between the nickel-platinum active ingredients and the carrier and enhance the stability of the supported catalyst, preferably, the third heat treatment is carried out in a reducing atmosphere, which is a mixed gas of hydrogen and nitrogen / helium / argon, wherein the proportion of hydrogen is 3-50%; the temperature of the third heat treatment is 100-300°C.
[0067] The third aspect of the present application also provides a proton exchange membrane fuel cell, which comprises the above-mentioned supported catalyst provided in the present application, or a supported catalyst prepared by the preparation method of the above-mentioned supported catalyst provided in the present application.
[0068] The above-mentioned supported catalyst provided in the present application has a stable chemical structure and a high oxygen reduction reaction activity. Applying it in a proton exchange membrane fuel cell can improve the electrocatalytic activity of the cathode oxygen reduction reaction (ORR) in the proton exchange membrane fuel cell and improve the electrochemical performance of the proton exchange membrane fuel cell.
[0069] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0070] Example 1
[0071] A supported catalyst hcp-Ni 100 Mo 6.7 @Pt 25 / C preparation method, comprising:
[0072] (1) nickel acetylacetonate containing 0.1 mol of Ni element, molybdenum acetylacetonate containing 0.0067 mol of Mo element, 800 g of octadecene, 500 g of oleylamine and 8 g (0.02 mol) of trioctylphosphine were mixed, nitrogen was introduced and the temperature was raised to 100° C., and vacuum was evacuated for 30 min, wherein the vacuum degree of the reaction system was 200 mbar; nitrogen was continued to be introduced, the temperature was raised to 220° C., and maintained for 2 h to obtain a nickel-molybdenum nanoparticle solution of HCP crystal form;
[0073] like Figure 1 hcp-Ni shown 100 Mo 6.7 The inner core TEM image shows that the particle size of nickel-molybdenum nanoparticles is relatively uniform and there is no agglomeration phenomenon; Figure 3 The XRD characterization results show that due to the very low Mo doping content, the peak shape is closest to the Ni#45-1027 with hcp structure, indicating that the nickel-molybdenum nanoparticles have a close-packed hexagonal structure, and its chemical formula is recorded as hcp-Ni 100 Mo 6.7 ;
[0074] (2) Platinum acetylacetonate containing 0.025 mol of Pt element, 57.6 g of 1,2-tetradecanediol, 200 g of oleylamine and 100 g of oleic acid were mixed, heated to 80° C. and maintained for 10 min to obtain a platinum precursor solution;
[0075] (3) In a nitrogen atmosphere, the platinum precursor solution prepared in step (2) is added dropwise to the nickel-molybdenum nanoparticle solution prepared in step (1), and the reaction is completed at 200° C. for 2 h, and the nickel-molybdenum-platinum active component is obtained after filtering and washing;
[0076] According to the transmission electron microscopy results (such as Figure 2 ) shows that the platinum atomic layer is successfully coated on the surface of the nickel-molybdenum nanoparticles to form a core-shell structure of nickel-molybdenum-platinum active ingredients, with the core being nickel-molybdenum nanoparticles and the shell being a platinum atomic layer, denoted as hcp-Ni 100 Mo 6.7 @Pt 25 The average particle size of the nickel-molybdenum-platinum active component is 17 nm, and the number of platinum atomic layers in the nickel-molybdenum-platinum active component is 4;
[0077] (4) Disperse 21.5 g of carbon black (Cabot, VULCAN XC72R) in 600 mL of cyclohexane, and add hcp-Ni dispersed in cyclohexane dropwise. 100 Mo 6.7 @Pt 25 After stirring, hcp-Ni 100 Mo6.7 @Pt 25 The catalyst was loaded on the surface of the activated carbon carrier, washed and dried to obtain the supported catalyst, which was recorded as hcp-Ni 100 Mo 6.7 @Pt 25 / C;
[0078] like Figure 4 hcp-Ni 100 Mo 6.7 @Pt 25 TEM images of the supported catalysts, hcp-Ni 100 Mo 6.7 @Pt 25 Successfully loaded on the surface of activated carbon carrier.
[0079] In the above step (1), the molar ratio of nickel acetylacetonate, molybdenum acetylacetonate, octadecene, oleylamine and trioctylphosphine is 1:0.067:31.7:18.7:0.22; in the step (2), the molar ratio of platinum acetylacetonate, 1,2-tetradecanediol, oleylamine and oleic acid is 1:10:30:14.
[0080] The supported catalyst hcp-Ni prepared above 100 Mo 6.7 @Pt 25 / C in hcp-Ni 100 Mo 6.7 @Pt 25 The loading amount is 50wt%; the molar ratio of Pt element, Ni element and Mo element is 25:100:6.7, that is, the molar ratio of the core to the shell is 4.268:1.
[0081] Example 2
[0082] A supported catalyst hcp-Ni 100 Zr 10 @Pt 33 / A method for preparing Sb-SnO2, comprising:
[0083] (1) Nickel acetate containing 0.1 mol of Ni element, zirconium acetylacetonate containing 0.01 mol of Zr element, 1263 g of octadecene, 1338 g of oleylamine and 37 g (0.1 mol) of trioctylphosphine were mixed, argon was introduced, the temperature was raised to 90° C., and vacuum was evacuated for 10 min, wherein the vacuum degree of the reaction system was 100 mbar; argon was continued to be introduced, the temperature was raised to 250° C., and the temperature was maintained for 0.5 h to obtain a nickel-zirconium nanoparticle solution of hcp crystal form; the chemical formula of the nickel-zirconium nanoparticles is recorded as hcp-Ni 100 Zr 10 ;
[0084] (2) Platinum acetylacetonate containing 0.033 mol of Pt element, 170.6 g of 1,2-hexadecanediol, 353 g of oleylamine, and 186.5 g of oleic acid were mixed, heated to 100° C., and maintained for 5 min to obtain a platinum precursor solution;
[0085] (3) Under an argon atmosphere, the platinum precursor solution prepared in step (2) was added dropwise to the nickel zirconium nanoparticle solution prepared in step (1), and the reaction was completed at 210° C. for 2.5 h. After filtering and washing, the nickel zirconium platinum active component was obtained, which was recorded as hcp-Ni 100 Zr 10 @Pt 33 ; The average particle size of the nickel-zirconium-platinum active component is 5 nm; the number of platinum atomic layers is 5;
[0086] (4) 20.45 g of Sb-doped SnO2 (prepared in the laboratory, Sb doped 5 wt%) was dispersed in 600 mL of cyclohexane and stirred, and hcp-Ni dispersed in cyclohexane was added dropwise. 100 Zr 10 @Pt 33 After stirring, it was loaded on the surface of the Sb-doped SnO2 carrier, and after washing and drying, a supported catalyst was obtained, which was recorded as hcp-Ni 100 Zr 10 @Pt 33 / Sb-SnO2.
[0087] In the above step (1), the molar ratio of nickel acetate, zirconium acetylacetonate, octadecene, oleylamine and trioctylphosphine is 1:0.1:50:50:1; and in the step (2), the molar ratio of platinum acetylacetonate, 1,2-hexadecanediol, oleylamine and oleic acid is 1:20:40:20.
[0088] The supported catalyst hcp-Ni prepared above 100 Zr 10 @Pt 33 / hcp-Ni in Sb-SnO2 100 Zr 10 @Pt 33 The loading amount is 60wt%, and the molar ratio of Pt element, Ni element and Zr element is 33:100:10.
[0089] Example 3
[0090] A supported catalyst hcp-Ni 100 V5@Pt 17 / CeO2 preparation method, comprising:
[0091] (1) Nickel sulfate containing 0.1 mol of Ni element, acetylacetonato vanadyl containing 0.005 mol of V element, 340 g of phenyl ether, 185 g of dodecylamine and 3.9 g (0.01 mol) of trioctylphosphine oxide were mixed, nitrogen was introduced and the temperature was raised to 100° C., and vacuum was evacuated for 5 min, wherein the vacuum degree of the reaction system was 80 mbar; nitrogen was continued to be introduced, the temperature was raised to 250° C., and maintained for 3 h to obtain a nickel-vanadium nanoparticle solution of hcp crystal form, the chemical formula of the nickel-vanadium nanoparticle was recorded as hcp-Ni 100 V5;
[0092] (2) Chloroplatinic acid containing 0.017 mol of Pt element, 31.3 g of 1,2-tetradecanediol, 41.1 g of hexadecylamine and 48 g of oleic acid were mixed, heated to 50° C., and maintained for 60 min to obtain a platinum precursor solution;
[0093] (3) Under nitrogen atmosphere, the platinum precursor solution prepared in step (2) was added dropwise to the nickel-vanadium nanoparticle solution prepared in step (1), and the reaction was maintained at 220° C. for 1 h. After filtering and washing, the nickel-vanadium-platinum active component was obtained, which was recorded as hcp-Ni 100 V5@Pt 17 ; The average particle size of the nickel-vanadium-platinum active component is 20nm; the number of platinum atomic layers is 2;
[0094] (4) Disperse 30.6 g of cerium oxide in 800 mL of cyclohexane and stir, and add hcp-Ni dispersed in cyclohexane dropwise. 100 V5@Pt 17 After stirring, hcp-Ni 100 V5@Pt 17 The catalyst was loaded on the surface of the cerium oxide support, washed and dried to obtain a supported catalyst, which was recorded as hcp-Ni 100 V5@Pt 17 / CeO2.
[0095] In the above step (1), the molar ratio of nickel sulfate, vanadium acetylacetonate, phenyl ether, dodecylamine and trioctylphosphine oxide is 1:0.05:20:10:0.1; in the step (2), the molar ratio of chloroplatinic acid, 1,2-tetradecanediol, hexadecylamine and oleic acid is 1:8.2:10:10.
[0096] The supported catalyst hcp-Ni prepared above 100 V5@Pt 17 hcp-Ni in CeO2 100 V5@Pt 17 The loading amount is 30wt%, and the molar ratio of Pt element, Ni element and V element is 17:100:5.
[0097] Example 4
[0098] A supported catalyst hcp-Ni 20 The preparation method of La1Co1@Pt4 / Ti4O7 comprises:
[0099] (1) Nitrogen was introduced into nickel acetate containing 0.1 mol of Ni element, lanthanum acetylacetonate containing 0.005 mol of La element, cobalt nitrate containing 0.005 mol of Co element, 400 g of benzyl ether, 353.7 g of trioctylamine and 20 g (0.05 mol) of tributylphosphine, and the temperature was raised to 80° C., and vacuum was evacuated for 60 min, wherein the vacuum degree of the reaction system was 200 mbar; nitrogen was continued to be introduced, the temperature was raised to 180° C., and the temperature was maintained for 3 h to obtain a nickel lanthanum cobalt nanoparticle solution of hcp crystal form, and the chemical formula of the nickel lanthanum cobalt nanoparticle was recorded as hcp-Ni 20 La1Co1;
[0100] (2) Potassium chloroplatinate containing 0.02 mol of Pt element, 46.5 g of 1,2-hexadecanediol, 55.6 g of dodecylamine and 67.8 g of oleic acid were mixed, heated to 70° C., and maintained for 15 min to obtain a platinum precursor solution;
[0101] (3) Under a nitrogen atmosphere, the platinum precursor solution prepared in step (2) was added dropwise to the nickel lanthanum cobalt nanoparticle solution prepared in step (1), and the reaction was completed at 150° C. for 3 h. After filtering and washing, the nickel lanthanum cobalt platinum active component was obtained, which was recorded as hcp-Ni 20 La1Co1@Pt4; the average particle size of the nickel lanthanum cobalt platinum active component is 10nm; the number of platinum atomic layers is 3;
[0102] (4) 17.1 g of Ti4O7 was dispersed in 500 mL of cyclohexane and stirred, and the nickel lanthanum cobalt platinum active component dispersed in the cyclohexane was added dropwise. After stirring, the nickel lanthanum cobalt platinum active component was loaded on the surface of the Ti4O7 carrier. After washing and drying, a nickel lanthanum cobalt platinum supported catalyst was obtained, which was recorded as hcp-Ni 20 La1Co1@Pt4 / Ti4O7.
[0103] In the above step (1), the molar ratio of nickel acetate, lanthanum acetylacetonate, cobalt nitrate, benzyl ether, trioctylamine and tributylphosphine is 1:0.05:0.05:32.7:10:1; in the step (2), the molar ratio of potassium chloroplatinate, 1,2-hexadecanediol, dodecylamine and oleic acid is 1:9:15:12.
[0104] The supported catalyst hcp-Ni prepared above 20 hcp-Ni in La1Co1@Pt4 / Ti4O7 20The loading amount of La1Co1@Pt4 is 40wt%, and the molar ratio of Pt element, Ni element, La element and Co element is 4:20:1:1.
[0105] Example 5
[0106] A method for preparing a supported catalyst hcp-Ni4@Pt1 / C, comprising:
[0107] (1) A mixture of nickel acetylacetonate containing 0.1 mol of Ni element, 800 g of octadecene, 500 g of oleylamine and 12 g (0.03 mol) of trioctylphosphine was introduced with argon gas, heated to 100° C., and evacuated for 30 min, wherein the vacuum degree of the reaction system was 180 mbar; argon gas was continued to be introduced, the temperature was raised to 220° C., and maintained for 2 h to obtain a nickel nanoparticle solution of the hcp crystal form;
[0108] (2) Platinum acetylacetonate containing 0.025 mol of Pt element, 57.6 g of 1,2-tetradecanediol, 200 g of oleylamine and 100 g of oleic acid were mixed, heated to 80° C., and maintained for 10 min to obtain a platinum precursor solution;
[0109] (3) under an argon atmosphere, the platinum precursor solution prepared in step (2) was added dropwise to the nickel nanoparticle solution prepared in step (1), and the reaction was completed at 200° C. for 2 h. After filtering and washing, a nickel-platinum active component was obtained, which was recorded as hcp-Ni4@Pt1; the average particle size of the nickel-platinum active component was 16 nm; and the number of platinum atomic layers was 4;
[0110] (4) 21.5 g of carbon black (Cabot, VULCAN XC72R) was dispersed in 600 mL of cyclohexane and stirred, and the nickel platinum active component dispersed in cyclohexane was added dropwise. After stirring, hcp-Ni4@Pt1 was loaded on the surface of the activated carbon carrier. After washing and drying, a supported catalyst was obtained, which was recorded as hcp-Ni4@Pt1 / C.
[0111] In the above step (1), the molar ratio of nickel acetylacetonate, octadecene, oleylamine and trioctylphosphine is 1:31.7:18.7:0.32; in the step (2), the molar ratio of platinum acetylacetonate, 1,2-tetradecanediol, oleylamine and oleic acid is 1:10:29.6:14.
[0112] The loading amount of hcp-Ni4@Pt1 in the supported catalyst hcp-Ni4@Pt1 / C prepared above is 50wt%, and the molar ratio of Pt element to Ni element is 1:4.
[0113] Example 6
[0114] The difference from Example 1 is that the amount of raw materials is changed so that the ratio of the total molar number of nickel element and molybdenum element in the inner core to the total molar number of platinum element in the shell is 2:1.
[0115] Example 7
[0116] The difference from Example 1 is that the amount of raw materials is changed so that the ratio of the total molar number of nickel element and molybdenum element in the inner core to the total molar number of platinum element in the shell is 10:1.
[0117] Example 8
[0118] The difference from Example 1 is that the amount of raw materials is changed so that the ratio of the total molar number of nickel element and molybdenum element in the inner core to the total molar number of platinum element in the shell is 6:1.
[0119] Example 9
[0120] The difference from Example 1 is that the amount of raw materials is changed so that the ratio of the total molar number of nickel element and molybdenum element in the inner core to the total molar number of platinum element in the shell is 12:1.
[0121] Example 10
[0122] The difference from Example 1 is that the loading amount of the nickel-platinum active component is 30 wt % based on the total weight of the supported catalyst.
[0123] Embodiment 11
[0124] The difference from Example 1 is that the loading amount of the nickel-platinum active component is 60 wt % based on the total weight of the supported catalyst.
[0125] Example 12
[0126] The difference from Example 1 is that the loading amount of the nickel-platinum active component is 20 wt % based on the total weight of the supported catalyst.
[0127] Example 13
[0128] The difference from Example 1 is that the molar ratio of nickel element to molybdenum element is 10:1, and the supported catalyst finally prepared is recorded as hcp-Ni 97 Mo 9.7 @Pt 25 / C.
[0129] Embodiment 14
[0130] The difference from Example 1 is that the molar ratio of nickel element to molybdenum element is 20:1, and the supported catalyst finally prepared is recorded as hcp-Ni 102 Mo 5.1 @Pt 25 / C.
[0131] Embodiment 15
[0132] The difference from Example 1 is that the molar ratio of nickel element to molybdenum element is 2:1, and the supported catalyst finally prepared is recorded as fcc-Ni 71.2 Mo 35.6 @Pt 25 / C.
[0133] Example 16
[0134] The difference from Example 1 is that the temperature of the first heating treatment is 100° C. and the time is 5 minutes; the temperature of the second heating treatment is 180° C. and the time is 0.5 hours.
[0135] Embodiment 17
[0136] The difference from Example 1 is that the temperature of the first heating treatment is 80° C. and the time is 60 min; the temperature of the second heating treatment is 250° C. and the time is 3 h.
[0137] Embodiment 18
[0138] The difference from Example 1 is that the temperature of the first heating treatment is 60°C; the temperature of the second heating treatment is 170°C.
[0139] Embodiment 19
[0140] The difference from Example 1 is that the molar ratio of nickel salt (nickel acetylacetonate), solvent (octadecene), first alkylamine (oleylamine) and alkyl phosphide (trioctylphosphine) is 1:20:10:0.1.
[0141] Embodiment 20
[0142] The difference from Example 1 is that the molar ratio of the nickel salt (nickel acetylacetonate), the solvent (octadecene), the first alkylamine (oleylamine) and the alkyl phosphide (trioctylphosphine) is 1:50:50:1.
[0143] Embodiment 21
[0144] The difference from Example 1 is that the molar ratio of nickel salt (nickel acetylacetonate), solvent (octadecene), first alkylamine (oleylamine) and alkyl phosphide (trioctylphosphine) is 1:15:5:0.01.
[0145] Embodiment 22
[0146] The difference from Example 1 is that the molar ratio of platinum salt (platinum acetylacetonate), reducing agent (1,2-tetradecanediol), alkylamine (oleylamine) and surfactant (oleic acid) is 1:20:40:10.
[0147] Embodiment 23
[0148] The difference from Example 1 is that the molar ratio of platinum salt (platinum acetylacetonate), reducing agent (1,2-tetradecanediol), alkylamine (oleylamine) and surfactant (oleic acid) is 1:8:10:20.
[0149] Embodiment 24
[0150] The difference from Example 1 is that the molar ratio of platinum salt (platinum acetylacetonate), reducing agent (1,2-tetradecanediol), alkylamine (oleylamine) and surfactant (oleic acid) is 1:5:5:21.
[0151] Embodiment 25
[0152] The difference from Example 3 is that the vanadium acetylacetonate in step (1) is replaced by silver nitrate containing 0.005 mol Ag element, and the other preparation processes are the same as those in Example 3; the supported catalyst finally prepared is recorded as hcp-Ni 100 Ag5@Pt 17 / CeO2.
[0153] Embodiment 26
[0154] The difference from Example 2 is that: in step (1), no vacuum operation is performed, and the temperature is directly raised to 250° C. and maintained for 0.5 h to obtain a nickel-zirconium nanoparticle solution. The other preparation processes are the same as those in Example 2; the finally obtained supported catalyst is recorded as hcp-Ni 100 Zr 10 @Pt 33 / Sb-SnO2 (not vacuumed).
[0155] Comparative Example 1
[0156] The difference from Example 1 is that in step (1), octadecene is not added, and only the same amounts of nickel acetylacetonate, molybdenum acetylacetonate, oleylamine and trioctylphosphine are mixed.
[0157] Depend on Figure 5 The TEM image of the core shown in the figure shows that the core particle size is uniform and there is no agglomeration phenomenon. Figure 7 From the XRD diagram of the core shown in FIG. 1 , it can be seen that the Mo doping content in the core prepared in Comparative Example 1 is very low, so the peak shape is closest to the fcc structure Ni#04-0850, and its crystal form is a face-centered cubic structure (fcc), which is recorded as fcc-Ni 100 Mo 6.7 .
[0158] Depend on Figure 6 The TEM image of the nickel-platinum active component shown in the figure shows that the platinum atomic layer is coated on the fcc-Ni 100 Mo 6.7The surface of the core forms a nickel-platinum active component, recorded as fcc-Ni 100 Mo 6.7 @Pt 25 The supported catalyst finally prepared in Comparative Example 1 is denoted as fcc-Ni 100 Mo 6.7 @Pt 25 / C.
[0159] It should be noted that the following tests were performed on the supported catalysts prepared in all the examples and comparative examples in this application, as well as commercial platinum carbon:
[0160] (1) Cyclic voltammetry: Cyclic voltammetry was performed in a nitrogen-saturated 0.1 mol / L HClO4 solution with a voltage range of 0.05 to 1.2 V (vs RHE) to obtain the electrochemical active area;
[0161] (2) Polarization curve test: Polarization curve test was carried out in a nitrogen-saturated 0.1 mol / L HClO4 solution with a voltage range of 0.1 to 1.2 V (vs RHE) to obtain the specific weight activity;
[0162] (3) Cyclic stability performance test: The test was carried out using a rotating disk electrode to test the performance degradation after 30,000 cycles at 0.6 to 1.0 V (vs RHE) and the performance degradation after 50,000 cycles at 1.0 to 1.5 V (vs RHE).
[0163] The test results are shown in Table 1 and Table 2.
[0164] Table 1
[0165]
[0166]
[0167] Table 2
[0168]
[0169] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0170] It can be seen from Table 1 and Table 2 that the oxygen reduction activity and durability of the supported catalysts in Examples 1 to 5 are better than those of commercial platinum carbon, among which hcp-Ni 100 Mo 6.7 @Pt 25 The specific weight activity of Pt / C is 3.3 times that of commercial Pt / C.
[0171] Comparing Examples 1 and 5, it can be seen that the supported catalyst with a nickel alloy as the core has better durability than the supported catalyst with a nickel as the core. This is because the strain of the nickel alloy core changes the lattice parameters, thereby enhancing the stability of the supported catalyst.
[0172] By comparing Examples 1 to 4, it can be seen that the durability of the catalyst with metal oxide as the carrier is better than that of the carbon-supported catalyst at 1.0-1.5 V (vs RHE), which indicates that the metal bond formed between the metal in the metal oxide carrier and Pt is stronger than the interaction between the carbon carrier and Pt, thereby making the metal oxide carrier-supported catalyst more stable in the high-potential durability test.
[0173] Comparing Examples 1, 6, 7 and 9, it can be seen that the molar ratio of the core to the shell includes but is not limited to the preferred range of the present application. Limiting it within the preferred range of the present application is beneficial to improving the coating effect and compactness of the platinum atomic layer on the core, inhibiting the precipitation of the nickel-containing core, thereby improving its durability, and also beneficial to the regulation of the geometry and electronic effects of the platinum atomic layer by the core, thereby improving activity. Comparing Examples 1, 6 to 8, it can be seen that limiting the molar ratio of the core to the shell within the further preferred range of the present application is beneficial to further improving the coating effect and compactness of the platinum atomic layer on the core, further inhibiting the precipitation of the nickel-containing core, thereby further improving its durability, and optimizing the regulation of the geometry and electronic effects of the platinum atomic layer by the core.
[0174] Comparing Examples 1, 10 to 12, it can be seen that when the loading is too small, the platinum active sites in the supported catalyst are less and the durability is poor. When used in a proton exchange membrane fuel cell, the catalyst layer of the membrane electrode is thicker, and its proton conductivity and oxygen mass transfer diffusion are adversely affected; when the loading is too large, the nickel-platinum active component is more likely to agglomerate, which may lead to a reduction in the electrochemical area and a reduction in metal utilization. The loading amount of the nickel-platinum active component includes but is not limited to the preferred range of this application, and limiting it to the preferred range of this application is conducive to improving the oxygen reduction reaction activity of the supported catalyst.
[0175] In Example 15, due to the addition of too much molybdenum, the hcp crystal form cannot be formed, and only the fcc crystal form can be formed. Comparing Examples 1, 13 to 15, it can be seen that the molar ratio of nickel element to molybdenum element includes but is not limited to the preferred range of the present application, and limiting it within the preferred range of the present application is conducive to the inner core maintaining its close-packed hexagonal structure (hcp) unchanged, and the doping of molybdenum element is conducive to further suppressing the problem of easy dissolution of the nickel-based inner core, and enhancing the stability of the nickel-molybdenum-platinum active component in the supported catalyst.
[0176] By comparing Examples 1 and 16 to 18, it can be seen that, compared with other ranges, using the temperature and time in the preferred range of the present application to treat the reaction system is beneficial to the synthesis of nickel-based active ingredients with more uniform particle size, and is also beneficial to inhibiting the oxidation of the nickel-based active ingredients, which is beneficial to the coating of the platinum atomic layer, thereby improving the oxygen reduction reaction activity of the supported catalyst.
[0177] By comparing Examples 1 and 19 to 21, it can be seen that the molar ratio of the nickel salt (nickel acetylacetonate), the solvent (octadecene), the first alkylamine (oleylamine) and the alkyl phosphine (trioctylphosphine) includes but is not limited to the preferred range of the present application. Limiting it within the preferred range of the present application is beneficial to improving the generation rate of the nickel-based active ingredient; at the same time, it is beneficial to obtain a nickel-platinum active ingredient with a more uniform particle size, thereby improving the activity.
[0178] By comparing Examples 1 and 22 to 24, it can be seen that the molar ratio of the platinum salt (platinum acetylacetonate), the reducing agent (1,2-tetradecanediol), the alkylamine (oleylamine) and the surfactant (oleic acid) includes but is not limited to the preferred range of the present application. Limiting it within the preferred range of the present application is beneficial to further improve the dispersibility of the platinum precursor, while further improving the coating effect of the subsequent platinum atomic layer.
[0179] By comparing Examples 1 to 4 and Example 25, it can be seen that compared with other types, the preferred types of non-nickel metal elements (such as Mo, Zr, V, La, Co, etc.) used in the present application can form a more stable nickel alloy with the nickel element, which is beneficial to avoid the dissolution of the nickel-based core and further improve the stability of the supported catalyst. At the same time, the preferred types of non-nickel metal elements used in the present application are beneficial to further improve the oxygen reduction reaction activity of the supported catalyst.
[0180] By comparing Examples 2 and 26, it can be seen that vacuuming the reaction system is beneficial to removing impurities produced by volatilization at high temperatures, so that the subsequently obtained nickel-zirconium nanoparticles have a more uniform particle size; it is also beneficial to remove oxygen dissolved in the solvent, thereby inhibiting the oxidation of the nickel-zirconium nanoparticles and facilitating the subsequent coating of the platinum atomic layer.
[0181] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0182] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A supported catalyst, characterized in that The supported catalyst comprises a nickel-platinum active component and a carrier, and the nickel-platinum active component is supported on the surface of the carrier; from the inside to the outside, the nickel-platinum active component comprises a core and a shell, and the molar ratio of the core to the shell is (2-10):1; the core is a nickel alloy, and the nickel alloy comprises nickel elements and non-nickel metal elements; the shell is a platinum atomic layer, and the shell is coated on the surface of the core; the crystal structure of the core is a close-packed hexagonal structure; The molar ratio of the nickel element to the non-nickel metal element is ≥10:1; the non-nickel metal element is selected from one or more of the group consisting of Sr, Ga, Sn, Bi, Fe, Co, Cu, Au, Sc, La, Ce, Sm, Ti, Zr, V, Mo and W.
2. The supported catalyst according to claim 1, characterized in that The molar ratio of the inner core to the outer shell is (2-6):
1.
3. The supported catalyst according to claim 1, characterized in that The loading amount of the nickel-platinum active component is 30-60 wt % based on the total weight of the supported catalyst.
4. The supported catalyst according to claim 1, characterized in that The molar ratio of the nickel element to the non-nickel metal element is (10-20):
1.
5. The supported catalyst according to claim 4, characterized in that The average particle size of the nickel-platinum active component is 5 to 30 nm.
6. The supported catalyst according to claim 5, characterized in that The average particle size of the nickel-platinum active component is 5 to 20 nm.
7. The supported catalyst according to claim 1, characterized in that The number of the platinum atomic layers is 1 to 6.
8. The supported catalyst according to claim 7, characterized in that The number of the platinum atomic layers is 2 to 4.
9. The supported catalyst according to any one of claims 4 to 7, characterized in that The carrier is a carbon carrier and / or a metal oxide carrier; The carbon carrier is selected from one or more of the group consisting of activated carbon, carbon black, graphite, graphene and acetylene black; The metal oxide carrier is selected from one or more of the group consisting of doped SnO2, TiO2, Ti4O7, CeO2, NbO, NbO2, Nb2O3, Nb2O5 and WO3.
10. The supported catalyst according to any one of claims 9, characterized in that The doped SnO2 includes a doping element, and the doping element is selected from one or more of the group consisting of Sb, Nb, In and W.
11. A method for preparing a supported catalyst according to claim 1, characterized in that: The preparation method of the supported catalyst comprises: Under the condition of a first inert atmosphere, a nickel salt, an organic solvent, a first alkylamine, an alkyl phosphide and an optional non-nickel metal salt are mixed and subjected to a staged temperature increase treatment to obtain a nickel-based active ingredient solution, wherein the non-nickel metal element in the non-nickel metal salt is an element type that can form an alloy with the nickel element; the organic solvent is selected from one or more of the group consisting of octadecene, phenyl ether and benzene ether; wherein the molar ratio of the nickel salt, the organic solvent, the first alkylamine and the alkyl phosphide is 1:(20-50):(10-50):(0.1-1); the staged temperature increase treatment includes a first temperature increase treatment and a second temperature increase treatment; the first temperature increase treatment includes: heating the reaction system to 80-100°C and then performing a vacuum treatment, and maintaining it for 5-60 minutes; the second temperature increase treatment includes: heating the mixed solution obtained after completing the first temperature increase treatment to 180-250°C and maintaining it for 0.5-3 hours; Under a second inert atmosphere, a platinum salt, a reducing agent and a second alkylamine are mixed and subjected to a first heating treatment to obtain a platinum precursor solution; wherein the molar ratio of the platinum salt, the reducing agent and the second alkylamine is 1:(8-20):(10-40); the temperature of the first heating treatment is 50-100° C., and the time is 5-60 min; Under the third inert atmosphere, the platinum precursor solution is mixed with the nickel-based active component solution and subjected to a second heating treatment to obtain a nickel-platinum active component; wherein the second heating treatment is performed at a temperature of 150 to 220° C. for 1 to 3 hours; The nickel-platinum active component is loaded on the surface of a carrier to obtain the loaded catalyst.
12. The method for preparing a supported catalyst according to claim 11, characterized in that: The nickel salt is selected from one or more of the group consisting of nickel acetylacetonate, nickel sulfate, nickel acetate, nickel chloride and nickel acetate; the platinum salt is selected from one or more of the group consisting of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, platinum acetylacetonate and platinum nitrate.
13. The method for preparing a supported catalyst according to claim 11, characterized in that: The vacuum degree of the vacuum treatment is 80-200 mbar.
14. The method for preparing a supported catalyst according to claim 11, characterized in that: The first alkylamine is selected from one or more of the group consisting of oleylamine, dodecylamine, hexadecylamine, octadecylamine, octylamine and trioctylamine; the alkyl phosphide is selected from one or more of the group consisting of trioctylphosphine, trioctylphosphine oxide and tributylphosphine.
15. The method for preparing a supported catalyst according to any one of claims 11 to 13, characterized in that: The reaction system of the first heat treatment further includes a surfactant.
16. The method for preparing a supported catalyst according to claim 15, characterized in that: The molar ratio of the platinum salt, the reducing agent, the alkylamine and the surfactant is 1:(8-20):(10-40):(10-20).
17. The method for preparing a supported catalyst according to claim 15, characterized in that: The reducing agent is selected from 1,2-dodecanediol and / or 1,2-tetradecanediol; the second alkylamine is selected from one or more of the group consisting of oleylamine, dodecylamine, hexadecylamine and octadecylamine; the surfactant is selected from one or more of the group consisting of oleic acid, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide.
18. A proton exchange membrane fuel cell, characterized in that: The proton exchange membrane fuel cell comprises the supported catalyst according to claim 1.
Citation Information
Patent Citations
A catalyst with ultra-low platinum content for fuel cell and preparation method thereof
CN109037715A
Supported platinum-based core-shell catalyst and preparation method thereof
CN110890558A
Nickel-platinum core-shell nanostructure material, synthesis method and application
CN114101664A
Core / shell-type catalyst particles and methods for their preparation
US20110086295A1